PENYULUHAN REBUSAN DAUN BINAHONG UNTUK MENURUNKAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI DESA SAMURA KABANJAHE - Rentawati Purba; Rostiodertina Girsang; Tedty Rohaya Tinambunan; Dewi Tiansa Barus; Hariati Hariati (INSTITUT KESEHATAN DELI HUSADA, 2021)
Hypertension is blood pressure above 140/90 mmHg. Hypertension, which generally has no known symptoms, which often affects a person, can be reduced or treated using herbal therapy, one of which is giving boiled water from binahong leaves to people with hypertension. Binahong leaves (Anredera cordifolia) are herbal leaves containing nitric oxidants and saponins that stabilize blood flow that carry nutrients to every cell tissue and lower cholesterol levels, as antioxidants, antivirals, anticarcinogens and lumen fermentation manipulators. This action is very practical, cheap and easy and can be done by everyone. This action is still rarely done by the public when experiencing increased blood pressure. This service was carried out on 10 elderly people who had hypertension and 15 people who did not have hypertension. The service implementation team provided training on how to make binahong leaf stew in Samura Kabanjahe village. Where Binahong leaves are very easy to get in this area. The team made home visits as an evaluation of the service program. The outreach activities went smoothly. There are some elderly asking about counseling material.